Efektivitas Model Pembelajaran Cooperative Learning Tipe Scramble Terhadap Membaca Permulaan Siswa Kelas II SDN Banyuajuh IV Kamal - Annisa Wasiaturrohmah; Tyasmiarni Citrawati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The background of this research is that 5 out of 10 students have difficulty recognizing and reading letters, syllables, words, and sentences. The purpose of this study was to determine the effectiveness of the scramble-type cooperative learning model for beginning reading of grade II elementary school students at SDN Banyuajuh IV Kamal to be precise. The research method used is quantitative research with experimental research types. However, this study also found that the use of the scramble type cooperative learning model also had a good effect on student activity. Data collection techniques used were interviews, questionnaires, observations and tests. This research was conducted in class II with a total of 10 students. Effectiveness is obtained from the Paired Sample T Test of 0.03 which if the Sig value is less than 0.05 then it can be said to be effective. The attractiveness of this model can be seen from the student response questionnaire. Based on the acquisition of these data, the Scramble Type Cooperative Learning learning model is appropriate for use for Beginning Reading Learning for Grade II Students at SDN Banyuajuh IV Kamal.